Optimal skin simulant for ballistic testing - Hes, R. A. G.; Painter, Jonathan; Appleby-Thomas, Gareth J. (Elsevier, 2023)
An extensive literature review, combined with practical experience of forensic testing, has identified several concerns regarding existing studies into skin simulants. These can be summarized as arising due to human skin being a highly complex, multi-layered and anisotropic material whose mechanical properties depend on many factors such as age and gender of the host. In many studies (and papers) essential information is missing. Although there is some parallelism between the studies, the reported energy density at perforation is very inconsistent (a function of the natural variation of skin properties alluded to above) and differs from 0,113 J/mm2 [1] to 0,239 J/mm2 [2]. Which is, in fact, a more than 100% variation. Such a variation is arguably insufficient to enable accurate replication with a single simulant material. Combined with the missing common agreement about the energy density threshold between countries, laboratories and researchers, this analysis clearly identifies the need for an adjustable and / or customizable skin simulant. To-date, the most often used simulation material for human skin in ballistic testing is ‘Chrome crusted cow hide’ [3]. However, this is a natural material and, consequently therefore, inevitably physically variable in nature – both inter and intra hide. Ballistic tests on 10 chrome crusted cow hides using 4,5 mm BB’s gave v50% ranging from 113 m/s to 200 m/s, an uncontrolled variability for forensic experiments. Hence, the authors examined a skin analogue that could be produced in-house, enabling tailoring to match the desired properties, and with improved consistency. To this end, a thin, 4 mm thick, layer of gelatine (30 – 45 weight %, increasing per 1 weight %) was studied. The ballistic resistance of the gelatine skin analogue was compared to the v50%’s published values in literature, with good agreement found as the gelatine concentration was varied. In comparison to the chrome crusted cow hides this suggests that this relatively simple and accessible approach has potential to provide a more consistent standard.
Keywords: Gelatine; shooting scene reconstruction; wound ballistics; skin simulant